The Royal School of Needlework book of embroidery a guide to essential stitches, techniques and projects - McDonald, Jacqui; Royal School of Needlework (London, England) (Tunbridge Wells, Kent Search Press, 2018)
This book is a rich source of embroidery techniques, stitches and projects, covering eight key subjects in detail: crewelwork, bead embroidery, stumpwork, canvaswork, goldwork, whitework, blackwork and silk shading. Containing all the trusted, bestselling content from the RSN Essential Stitch Guide series, plus a new section on mounting your finished work. Written by expert RSN graduate apprentices and endorsed by the RSN, the book contains clear step-by-step stitch guides, examples of contemporary and historical pieces and inspiring projects
Crewelwork / by Jacqui McDonald, 2010 -- Canvaswork / by Rachel Doyle, 2013 -- Blackwork / by Becky Hogg, 2010 -- Silk shading / by Sarah Homfray, 2011 -- Goldwork / by Helen McCook, 2012 -- Stumpwork / by Kate Stinton, 2011 -- Whitework / by Lizzy Lansberry, 2012 -- Bead embroidery / by Shelly Cox, 2013
Contains material previously published as 8 separate titles as part of the RSN Essential Stitch Guide series
1
Keywords: Embroidery -- Patterns; Embroidery